EVALUATION OF EDUCATIONAL SERVICES USING SPATIAL ANALYSIS AND GIS (AL HUSSAINYEH CITY AS CASE STUDY) - M.J. Al Sharaa, Hisham (Journal of Engineering and Sustainable Development, 2016)
Geographical Information Systems (GIS) becoming useful and important tools for making strategic decisions whenever trusted data are found to have spatial distribution, finding suitable sites for educational areas are important, like Schools which are located in a strategic and safe area play an important role for buildup students’ abilities in future. Therefore, the aim of the present work is to Study firstly, the evaluation of educational services in the two cities (Al Hussainyeh & Imam Oun) within their regional context and to recommend long term options for their development. Secondly, it aims to outline the necessary actions that shall ensure the orderly development of expansion of educational needs within urban limits, make a Spatial analyzing for educational services in Al Hussainyeh city, It was carried out by geographic information system (GIS) as a tool for multi-criteria spatial analyzing. the results with some implemented standards based on (GIS) using ArcGIS info-10.2.1 spatial and analysis tools and Excel office as statistical software.